Efek Metode Pengeringan Terhadap Kandungan Bahan Kimia Dalam Rumput Laut Sargassumpolycystum - Masduqi, Ahmad Fuad; Izzati, Munifatul; Prihastanti, Erma (BULETIN ANATOMI DAN FISIOLOGI dh SELLULA, 2014)
Sargassum polycystum as a seaweed that contains several chemical. Chemical in Sargassum polycystum is potential to be exploited and developed. Post harvest handling of Sargassum polycystum is very important, especially in drying method. Drying method will affect the chemical contentin Sargassum polycystum. The aims of this research is to study the effect of drying methods to the chemical in Sargassum polycystum. This research is conducted in the Biology laboratory, department of Biology faculty of Sains and Mathematics Diponegoro University. This research was designed by random complete design. The research was the methods of drying (under the sun, using the oven and wind drying), each treatment were replicated 3 times. The resulted data was analized by Analysis of Variance (ANOVA) continued by real difference test Duncan Multiple Range Test (DMRT) in 95% significance level. The parameters in this research were the content of total phenols, alginate, proximate (ash content, water, fat, crude protein and crude fiber). Beside that, the effectivity of Sargassum polycystum flour for fish presertative were also examined by calcuting the number of bacteria and organoleptic parameters, including the freshness, durability and fish performance. The result showed that drying methods affect the content of total phenols, alginate and proximate of Sargassum polycystum. Wind drying method is the most efficient drying in getting the phenolic compounds (at 1656.3ppm).